Psycholinguistic Challenges in English Learning for Uzbek Speakers - Raxmanova Dilobar (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This study examines the psycholinguistic challenges faced by Uzbek speakers in learning English as a foreign language. Differences in phonetics, morphology, syntax, and pragmatics between Uzbek and English create specific cognitive and linguistic obstacles that affect comprehension, speech production, and communicative competence. Uzbek learners often encounter difficulties in word order, tense usage, article application, and idiomatic expressions due to cross-linguistic interference. Furthermore, sociocultural and cognitive factors, including language habits, context-dependent meaning, and mental processing strategies, influence the learning process. By analyzing these challenges, the study aims to provide practical recommendations for English language teaching and to enhance learners’ psycholinguistic awareness, ultimately improving fluency and accuracy in communication.